Aqueous extract of yellow maca (Lepidium meyenii) improves sperm count in experimental animals but response depends on hypocotyl size, pH and routes of administration - Sanchez-Salazar L. (2018)
Lepidium meyenii, a Peruvian plant growing over 4000 m.a.s.l., has effects on nutrition and fertility. The purpose of this study was to evaluate the sperm count in 105 male mice receiving boiled aqueous extract of yellow maca hypocotyls from different sizes, under different pH conditions and using two different routes of administration. Five mice per group were treated daily for 3 days with vehicle (oral and intraperitoneal) or maca aqueous extracts (5 mg/0.5 ml/day) belonging to the first, second, third and fourth categories, according to their hypocotyl size. On day four, sperm count was evaluated at testis, epididymis and vas deferens. Sperm count was higher in mice receiving maca from the larger sizes (first and second categories). Reduction in maca extract pH increased sperm count, whereas an increase in the pH resulted in a reduction in sperm count. The effect of pH reduction is observed only in maca from the first and second categories. Aqueous extract of maca was effective only after oral administration. In conclusion, the larger size of hypocotyls presented the best biological effect, and the low pH in the extract and the transformation after gastrointestinal passage are both important for its biological action.